A qualitative study of sexual and reproductive health communication with adolescent and young adult oncology patients. Issue 6 (15th February 2019) - Frederick, Natasha N.; Revette, Anna; Michaud, Alexis; Bober, Sharon L.
Abstract: Background: Adolescent and young adult patients with cancer (AYAs) identify sexual and reproductive health (SRH) as an important but often neglected aspect of their comprehensive cancer care. The purpose of this study was to explore AYA perceptions and experiences of SRH communication with oncology clinicians. Methods: Twenty‐three AYA patients and survivors ages 15‐25 years from a large academic oncology center participated in semistructured qualitative interviews investigating their experiences discussing SRH issues, including specific topics discussed, conversation barriers and facilitators, suggestions for clinicians on how to improve conversations, and education and resource needs. Interviews were audio recorded, transcribed, and coded using a thematic analysis approach. Results: Interviews with AYAs revealed two primary themes—a need for oncology clinicians to discuss SRH and critical gaps in current SRH communication practices. AYAs reported a need for improved SRH communication for the purposes of general education, addressing specific SRH issues experienced, and understanding the long‐term impact of cancer and treatment on SRH. The current communication gaps are exacerbated by patient discomfort initiating conversations and the presence of family members. AYAs shared six key recommendations for clinicians on how to improve SRH communication. Conclusions: AYAs identify a role for oncology clinicians in discussing SRH as a primary aspect of comprehensive health care during cancer treatment and in survivorship; however, multiple gaps and barriers interfere with such discussions. Future efforts must focus on clinician education and training in SRH as well as education and intervention opportunities for AYAs to optimize the care provided.